Cinobufagin Induces Cell Cycle Arrest at the G2/M Phase and Promotes Apoptosis in Malignant Melanoma Cells - Pan, Zhaohai; Zhang, Xin; Yu, Pengfei; Chen, Xiaoyu; Lu, Peng; Li, Minjing; Liu, Xiaona; Li, Zhipeng; Wei, Fei; Wang, Kejun; Zheng, Qiusheng; Li, Defang (Frontiers in Oncology, 2019)
Emerging evidence has shown that cinobufagin, as an active ingredient of Venenum Bufonis, inhibits tumor development. The aim of this study was to investigate the inhibitory effects of cinobufagin on A375 human malignant melanoma cells. MTT and colony formation assays showed that cinobufagin significantly inhibited A375 cell proliferation and cell colony formation. Additional studies demonstrated that cinobufagin markedly increased the levels of ATM serine/threonine kinase and checkpoint kinase 2 and decreased the levels of cell division cycle 25C, cyclin-dependent kinase 1, and cyclin B, subsequently inducing G2/M cell cycle arrest in A375 cells. Moreover, cinobufagin clearly inhibited the levels of phosphoinositide 3-kinase (PI3K), phosphorylated PI3K (p-PI3K), AKT, p-AKT, and B-cell lymphoma 2 (Bcl-2). By contrast, it increased the levels of Bcl-2-associated death promoter, Bcl-2-associated X, cytoplasmic cytochrome C, and apoptotic protease activating factor 1, leading to increased levels of cleaved caspase-9 and cleaved caspase-3, resulting in the apoptosis of A375 cells. Together, these results indicate that cinobufagin can induce cell cycle arrest at the G2/M phase and apoptosis, leading to inhibition of A375 cell proliferation. Thus, cinobufagin may be useful for melanoma treatment.